IMPLEMENTASI KURIKULUM DALAM PEMBELAJARAN PADA MASA PANDEMI COVID-19 - Basyiruddin, Mirza; Rukayah, Rukayah; Roemintoyo, Roemintoyo (Universitas Muhammadiyah Magelang, 2021)
The implementation of the learning curriculum during the Covid-19 pandemic is a challenge in the world of education. This study aims to reveal the implementation of the actual curriculum in the form of a combination of the core curriculum and the hidden curriculum through the analysis of learning activities during the Covid-19 pandemic. The subjects of this study were students of grade 6 SD Negeri Kalimacan, Kalijambe District, Sragen Regency which took place in the 1st semester of the 2020-2021 academic year. This study uses a qualitative approach method that is suitable in describing the problems that occur in the field. This type of qualitative research is a case study. The case study was chosen because of its suitability with a special ongoing problem, namely the implementation of the curriculum during the Covid-19 pandemic. Data collection techniques using interviews, observation, document analysis. The various data collected are then processed through the stages of data reduction, presentation, and drawing conclusions. Data validity trials were carried out through source and technique triangulation techniques. The results of this study indicate that the implementation of the curriculum during the Covid-19 pandemic was carried out by adjusting learning activities. The adjustment of these learning activities is by implementing the core curriculum and hidden curriculum through online and offline learning.